High salt-induced osmotic stress differentially modulates hepatocellular and renal carcinoma cell proliferation - Chen, Xi; Rahman, Asadur; Kitada, Kento; Wang, Yaoyu; Nakajima, Yoshihiro; Liu, Changjin; Taoka, Rikiya; Nishiyama, Akira (Frontiers in Oncology, 2026)
IntroductionHigh salt has been shown to affect cancer cell proliferation, however, its relationship with tumor growth remains controversial and mechanistically unclear. This study aims to elucidate how elevated sodium levels impact cell proliferation in hepatocellular carcinoma (HepG2) and renal carcinoma (Caki-1) cells, particularly under conditions of osmotic stress.MethodsCells were exposed to high salt (50 mM NaCl above basal medium) and assessed their proliferation and the expression of NFAT5, a crucial osmoprotective transcription factor. The role of NFAT5 was further examined using targeted knockdown or overexpression in both cell lines. Xenograft models were also established using HepG2 or Caki-1 cells in immunocompromised mice, which were fed either a normal-salt (0.3% NaCl chow + tap water) or high-salt (4% NaCl chow + 1% NaCl water) diet. ResultsHigh salt conditions led to a significant reduction in the proliferation of HepG2 cells both in vitro and in vivo, correlating with increased NFAT5 mRNA expression, while overexpression of NFAT5 effectively reversed this inhibition. Conversely, in Caki-1 cells, high salt did not significantly impact proliferation, tumor growth, or NFAT5 expression. However, NFAT5 knockdown in Caki-1 cells led to increased sensitivity and reduced proliferation in high-salt condition. Similar trends were observed with non-ionic osmoles (mannitol and sorbitol), which suppressed HepG2 cell proliferation without affecting Caki-1 cells. ConclusionTaken together, these findings indicate the potential role of osmotic stress tolerance in the differential effects of hypertonic environments on HepG2 and Caki-1 cell proliferation, highlighting NFAT5 and associated osmoadaptive mechanisms as promising therapeutic targets within the tumor microenvironment.